Persistence and Tissue Distribution of DNA in Normal and Immunodeficient Mice Inoculated with Polyomavirus VP1 Pseudocapsid Complexes or Polyomavirus - Heidari, S. (American Society for Microbiology, 2000)
Introduction of DNA into normal and immunodeficient mice, alone or in complex with VP1 pseudocapsids, has been compared to DNA transfer by viral infection. Similar to natural infection and in contrast to plasmid alone, VP1 pseudocapsids efficiently introduced DNA, which remained for months in normal mice and possibly longer in B- and T-cell-deficient mice.